2013
DOI: 10.5773/rgsa.v7i2.726
|View full text |Cite
|
Sign up to set email alerts
|

A Atuação No Mercado Externo Influencia a Estratégia De Gestão Ambiental Das Empresas Brasileiras? Um Estudo Multicaso Na Indústria Cerâmica De Santa Catarina

Abstract: RESUMO O objetivo geral deste trabalho é analisar a influência da atuação das estratégias de gestão ambiental das maiores empresas cerâmicas brasileiras no mercado externo. Os fundamentos teóricos discutem a gestão ambiental e seus aspectos determinantes, com ênfase nos requisitos e padrões do mercado externo, os quais exigem da empresa nacional seu enquadramento aos ditames de qualidade definidos no país de destino de seus produtos, assim como regulamentações referentes às questões ambientais e atitudes empre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
0
0
1
Order By: Relevance
“…In the descriptive analysis, approximately 86% of the companies under study had no ISO 14001 certification and only 56% publish their actions in social reports or Global Reporting Initiative. This corroborates the study by Alperstedt, Quintella, Martignago and Bulgacov (2013) that identified a lack of ISO 14001certification in ceramics companies due to the fact that their clients had their own checklists and did not require the companies to obtain certification.…”
Section: Analysis and Details Of Canonical Functionssupporting
confidence: 78%
“…In the descriptive analysis, approximately 86% of the companies under study had no ISO 14001 certification and only 56% publish their actions in social reports or Global Reporting Initiative. This corroborates the study by Alperstedt, Quintella, Martignago and Bulgacov (2013) that identified a lack of ISO 14001certification in ceramics companies due to the fact that their clients had their own checklists and did not require the companies to obtain certification.…”
Section: Analysis and Details Of Canonical Functionssupporting
confidence: 78%
“…Há autores que se dedicam a diferenciar as estratégias proativas daquelas chamadas reativas (Buysse & Verbeke, 2003;Porter & Van der Linde, 1995). Há aqueles que detalham as estratégias proativas, de acordo com o tipo de iniciativa empreendida na organização, (Alperstedt, Quintella, Martignago, & Bulgacov, 2013;Hart & Dowell, 2010;Orsato, 2006;Walker, Ni, & Huo, 2014 implementar na empresa tecnologias de prevenção da poluição por meio da introdução de produtos e processos, (re)concepção ou adaptação (Alperstedt et al, 2013;Christmann, 2000;Orsato, 2006); e, (iii) ser refletido nos valores corporativos e de gestão e integrados nos sistemas de gestão, relatórios de sustentabilidade e estratégia de negócios (Hart, 1995;Russo & Fouts, 1997;Walker et al, 2014 antipoluição nos produtos e processos da empresa (Hart & Dowell, 2010;Orsato, 2006); (ii) considerar a implantação de programas de qualidade na gestão ambiental (Shrivastava, 1995); e (iii) melhorar os processos produtivos (Alperstedt et al, 2013;González-Benito & González-Benito, 2006 responsabilidade ambiental de modo a promover sua imagem (Brønn & Vrioni, 2001). …”
Section: Sustentabilidade Ambientalunclassified